Non-dementia cognitive disorders: clinical aspects - T. L. Vizilo; A. D. Vizilo (Лечащий Врач)
Cognitive disorders are one of the most important problems of health of elderly patients. Due to absence of effective treatment on the stage of clinical dementia, great attention is paid to non-dementia cognitive disorders: moderate, mild, and subjective ones.